Petroleum Investment Patterns in Iraq The Transition Period (2003-2012) - Shaalan, Hisham Yas (Journal of Petroleum Research and Studies, 2016)
Iraq has huge oil and gas resources in terms of hydrocarbon reserves and high levels of expected production and export capabilities. Since 2003, dramatic political and economic changes have occurred, and these changes have affected the nature of, and trends within the Iraqi economy, mainly the petroleum industry which is the backbone of the Iraqi economy. There has been a radical shift in economic philosophy, to encourage new petroleum investment trends whereby the role of government is reduced and that of International Companies is enhanced, with the adoption of new investment patterns in upstream and downstream activities. These changes have occurred over a transition period for the institutional legal framework after 2003, and have introduced unprecedented patterns in most Iraqi petroleum activities. The subject of this paper is the fundamental changes in investment in relation to the Iraqi petroleum industry. The purpose of this paper is to examine the current and expected patterns of petroleum investment in Iraq into upstream and downstream activities during the period of 2003 2012. Note: Public Private Partnership (PPP), Build (B), Operate (O), Owned (O), Transfer (T).